Efficiency of polymyxin B treatment against nosocomial infection: a systematic review and meta-analysis - Peng, Liyuan; Zhang, Zhongheng; Qi, Xueyan; Zhong, Yanjun; Sun, Tongwen; Chen, Lvlin; Zhu, Junchen; Lv, Xiangui; Ma, Penglin (Frontiers in Medicine, 2024)
Background Some cohort studies have explored the effects and safety of polymyxin B (PMB) in comparison to other antibiotics for the treatment of nosocomial infections, yielding inconsistent results. This systematic review aims to explore the effectiveness and safety of PMB and compared it with other antibiotics. Methods A systematic literature search was conducted in PubMed, Embase, the Cochrane Library, and Web of Science, searching specific terms to identify quantitative cohort studies or RCTs that compared the effects of PMB with other antibiotics in terms of their efficacy and safety. The Newcastle–Ottawa Scale (NOS) was conducted to evaluate the risk of bias of observational studies. Odds ratios with 95% confidence intervals were used for outcome assessment. We evaluated heterogeneity using the I2 test. Results A total of 22 observational trials were included in the analysis. The PMB group had a higher mortality rate compared to the control group (odds ratio: 1.84, 95% CI: 1.36–2.50, p<0.00001, I2 = 73%). while, the ceftazidime-avibactam group demonstrated a distinct advantage with lower mortality rates, despite still exhibiting high heterogeneity (odds ratio 2.73, 95% confidence interval 1.59–4.69; p = 0.0003; I2 = 53%). Additionally, the PMB group had a lower nephrotoxicity rate compared to the colistin group but exhibited high heterogeneity in the results (odds ratio 0.58, 95% CI 0.36–0.93; p = 0.02; I2 = 73%). Conclusion In patients with nosocomial infections, PMB is not superior to other antibiotics in terms of mortality, specifically when compared to ceftazidime-avibactam. However, PMB demonstrated an advantage in terms of nephrotoxicity compared to colistin.